Analytical Conversion of Conventional Car to Electric Vehicle Using 5KW BLDC Electric Motor - Fuad Zainuri; Danardono A.S Danardono A.S; M. Adhitya; R. Subarkah; Rahman Filzi; Tia Rahmiati; M. Hidayat Tullah; Sonki Prasetya; Rahmat Nova; M. Todaru; M. Ridwan (Jurnal Penelitian Pendidikan IPA, 2024)
The automotive industry is witnessing a paradigm shift towards sustainable and eco-friendly transportation solutions. This project aims to contribute to this transition by converting a conventional internal combustion engine (ICE) car into an electric vehicle (EV) using a 5 kW Brushless DC (BLDC) electric motor. The conversion involves the removal of the traditional engine components and the integration of an electric propulsion system. The key components of the conversion include the BLDC motor, motor controller, battery pack, and associated power electronics. The BLDC motor is chosen for its efficiency, reliability, and compact design, making it suitable for retrofitting into existing vehicles. The motor controller manages the power supplied to the BLDC motor, ensuring optimal performance and efficiency. The project explores the challenges and solutions encountered during the conversion process, including adapting the vehicle's chassis to accommodate the new components, integrating a charging system, and addressing safety considerations. Additionally, efforts are made to optimize the overall weight distribution and maintain the vehicle's original handling characteristics. Performance testing is conducted to evaluate the acceleration, top speed, and overall efficiency of the converted electric vehicle. The results are compared with the original performance specifications of the conventional car to assess the success of the conversion. This project not only showcases the technical feasibility of converting conventional cars to electric vehicles but also highlights the environmental benefits associated with reducing reliance on fossil fuels. The findings contribute valuable insights to the growing field of electric vehicle conversions and promote sustainable transportation solutions.